Decision Making for Children with Obstructive Sleep Apnea without Tonsillar Hypertrophy. (March 2016) - Ishman, Stacey L.; Tang, Alice; Cohen, Aliza P.; Elhadi Babiker, Haithem; Chini, Barbara; Ehsan, Zarmina; Fleck, Robert J.; Gordon, Christopher; McPhail, Gary L.; Pan, Brian; Saal, Howard M.; Shott, Sally R.; et al.
Objective: Evidence-based medicine is the gold standard practice model for patient management. Our aim was to determine whether decisions made by pediatric subspecialists regarding management of obstructive sleep apnea in children without tonsillar hypertrophy adhered to this model or were based on clinical experiences. Study Design: Single-institution prospective study. Setting: Multidisciplinary upper airway center in an academic pediatric hospital. Subjects and Methods: Twelve pediatric subspecialists representing 8 specialties participating in upper airway clinics and management conferences. Real-time decisions made in treatment conferences and upper airway clinics were collected. Physicians were queried regarding the basis of their decisions, and these decisions were then classified into 10 categories. Results: Over 13 days (10 case conferences, 3 half-day clinics), 324 decisions were made for 58 patients (mean age = 8.9 ± 7.4 years, mean body mass index percentile = 75 ± 29); 34% (n = 108) of decisions were evidence based; 59% (n = 193) were nonevidence based; and 7% (n = 23) were based on parental preference. Providers were able to cite specific studies for <20% of these decisions. There was no significant increase in the proportion of evidence-based decisions made over time. Conclusions: We deemed 34% of decisions regarding the management of obstructive sleep apnea in children without tonsillar hypertrophy to be evidence based and found that sharing the basis for decisions did not improve the percentage of evidence-based decisions over time. These findings reflect significant evidence gaps and highlight the need for a systematic literature evaluation to identify best practice in managing this population. We recommend that these evidence gaps be further characterized and incorporated into an agenda for future research.